PENGARUH MANAJEMEN LABA DAN KARAKTERISTIK PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Bagaskara, Garin Fadh; Mulyana, Ricky A. (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research has the intention to gather empirical evidence on whether the net profit, operating cash flow, working capital, earnings management, leverage, company size and profitability can affect financial distress. This research involved data on 495 companies in the Consumer Cyclicals and Consumer Non-Cyclicals sectors listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Overall, a total of 165 companies were obtained with a research sample of 495 data. Sample selection used the purposive sampling method, while data analysis was using the binary logistic regression method. The outcomes obtained indicate that net profit, working capital, and company size influence financial distress. Large companies with positive profits tend to be considered financially healthier and easier to manage resources and obtain investment so as to avoid financial distress. Meanwhile, operating cash flow, earnings management, leverage and profitability do not affect financial distress